2018
DOI: 10.5424/fs/2017263-11547
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Functional genetic diversity of chestnut (Castanea sativa Mill.) populations from southern Spain

Abstract: Aim of the study: To evaluate the adaptive genetic variability of chestnut (Castanea sativa Mill.) populations from southern Spain in relation to bud burst and water stress.Area of study: Andalusia (southern Spain) where many chestnut groves were progressively abandoned and have become 'naturalized'. Material and methods:A total of 126 chestnut trees from eight populations were assessed by means of nine genic microsatellite loci (expressed sequence tag simple sequence repeat markers) related to bud burst and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Because said work suggested that the high levels of genetic diversity found in Central Italy indicate that this area was a refuge for sweet chestnut, we cannot rule out the possibility that in the areas studied in our work some remnants of old chestnut trees can also be found. Moreover, values of expected heterozygosity are in agreement with those obtained from other European chestnut populations [40,41], which is particularly evident in the work of Lusini et al [42], where six populations from Bulgaria were assessed using eight SSRs and whose H e values were in the range of 0.67-0.80.…”
Section: Discussionsupporting
confidence: 88%
“…Because said work suggested that the high levels of genetic diversity found in Central Italy indicate that this area was a refuge for sweet chestnut, we cannot rule out the possibility that in the areas studied in our work some remnants of old chestnut trees can also be found. Moreover, values of expected heterozygosity are in agreement with those obtained from other European chestnut populations [40,41], which is particularly evident in the work of Lusini et al [42], where six populations from Bulgaria were assessed using eight SSRs and whose H e values were in the range of 0.67-0.80.…”
Section: Discussionsupporting
confidence: 88%
“…Nine EST-SSRs were successfully transferred to our C. sativa material and showed considerable polymorphism. Although these markers are less polymorphic than neutral markers, several studies have highlighted their efficiency in assessing adaptive genetic diversity (Varshney et al, 2005;Luikart et al, 2003;Martín et al, 2010Martín et al, , 2017Cuestas et al, 2017;Alcaide et al, 2019). We identified CsPT_0005 as an outlier locus potentially under positive selection with private alleles for tolerant C. sativa trees.…”
Section: Assessment Of Adaptive Genetic Diversity To Pc and Selection...mentioning
confidence: 91%
“…Different European chestnut ecotypes may have origin in an overall high genetic diversity ( Villani et al, 1991 ; Pereira-lorenzo et al, 2010 ; Cuestas et al, 2017 ; Poljak et al, 2017 ; Alessandri et al, 2020 ; Bouffartigue et al, 2020 ). Dinis et al (2011a) and Pereira-Lorenzo et al (2011) found, with the use of SSR markers, that the diversity in chestnut orchards was greatly due to hybridization and discretely due to mutations.…”
Section: Abiotic Stresses Of C Sativamentioning
confidence: 99%